The Parsortix™ Cell Separation System—A versatile liquid biopsy platform. Issue 12 (14th August 2018) - Miller, M. Craig; Robinson, Peggy S.; Wagner, Christopher; O'Shannessy, Daniel J.
Abstract: Cancer cells from solid tumors can enter the circulatory system and survive to subsequently form distant metastases. The CellSearch® system (Menarini‐Silicon Biosystems, Huntingdon Valley, PA) was the first, FDA‐cleared system that provided a reliable tool for the investigation of circulating tumor cells (CTCs), which have been shown to be strongly associated with poor survival and therapy failure. Since that time, a number of new technologies have been introduced to improve CTC detection and/or isolation for further characterization. The continued and growing interest in the "liquid biopsy" field has spurred the development of numerous different CTC technologies. However, selecting the most appropriate CTC platform for individual applications can be challenging. No consensus has yet been reached in the community regarding which liquid biopsy technology is optimal. Here, we introduce the Parsortix™ Cell Separation System (ANGLE North America, Inc., King of Prussia, PA), a microfluidic based technology that captures rare cells based on size and deformability, offers reproducibly high capture efficiency, and produces highly enriched, viable (viability dependent on preservative used) CTCs that are amenable to a multitude of downstream analyses, including the isolation and interrogation of single cells. © 2018 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry.